IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DI MTS MINHAJUL HAQ PURWAKARTA - Nugraha, Agung; Al Mufti, Muflihin; Murtafiah, Nurul Hidayati (UNISAN JURNAL, 2025)
This research aims to: (1) understand the implementation of Madrasah-based management at MTs Minhajul Haq Purwakarta, and (2) identify the supporting and inhibiting factors in the implementation of Madrasah-based management at MTs Minhajul Haq Purwakarta. The type of research used is qualitative descriptive research, with a phenomenological approach, and data collection methods include interviews and documentation. The data analysis technique in this research uses data reduction, data presentation, and conclusion drawing. The data sources in this study are the headmaster, the vice principal of curriculum, the person in charge of facilities and infrastructure, and several teachers. The research results show that the implementation of Madrasah-based management at MTs Minhajul Haq Purwakarta regarding Madrasah-based management components, which include curriculum management and teaching programs, consists of three indicators: learning planning, implementation of learning, and learning evaluation, all of which are running well. The management of facilities and infrastructure, from planning to accountability, has not been well implemented due to financial constraints at the school. However, procurement and maintenance are categorized as good, as they are well managed and maintained. The management of students, from admissions, guidance, and organizational empowerment, is fully running well. In addition, extracurricular activities such as scouting, green farming, and martial arts, which directly build students' character, are also running well. The implications of this research are: (1) The headmaster plays a significant role in managing the school's situation and conditions, student and teacher discipline, as well as the procurement and maintenance of facilities and infrastructure. (2) To utilize supporting factors in the implementation of school-based management to achieve the goals and expectations optimally. (3) To anticipate inhibiting factors so that their impact can be minimized